A Multiquery analysis of a PeWEC farm (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The maximization of the power output of an array of wave energy converters (WECs) and its impact on the surrounding area are two fundamental, strictly interconnected, aspects that must be considered in the design of a wave farm. The effect of those two elements combined, usually considered separately, is evaluated, in this study, for a small farm of floating devices. The numerical simulations are performed using a coupled model between the BEM solver Capytaine (near-field solution) and the wave propagation model MILDwave (far-field solution). The farm is located off the coast of Pantelleria Island and is composed of three PeWECs, WECs designed for the Mediterranean Sea. The power output and the perturbed wave field around the PeWEC farm are compared to the single device, for different distances among the WECs. Moreover, a Power Take-Off (PTO) is implemented for assessing the difference in the far-field effects between a controlled and an uncontrolled case. Results show that the wake produced by the PeWEC farm is more prominent and more complex with respect to the single device. The inclusion of the PTO contributes to further attenuate the wave field in the lee of the PeWEC farm.